Fleet dynamics in multispecies trawlers: a study based on fisheries-dependent data - Fonseca, Tereza Cristina Pilar (2013)
Fishery-dependent data from the Portuguese coastal fish trawl fleet were integrated to examine fleet segmentation and dynamics along a 13-year period, and estimate speciesdirected effort and abundance. Six landing profiles (LPs) were based on the relative importance of target and by-catch species, including horse mackerel (Trachurus trachurus) and blue whiting (Micromesistius poutassou) almost exclusive LPs, three others corresponding to trips targeting squids (Loligo spp.), horse mackerel and octopuses, as the main species. LPs were assigned to trawlers, defining fleet components with specific technical characteristics and fishing strategies. This showed that large vessels target pelagics along the entire coastline, average-powered units fished a diverse catch off the Central zone of the western coast, including horse mackerel and cephalopods and a group of trawlers targeted cephalopods and benthic species off the south coast. Vessel Monitoring System (VMS) data, processed by GeoCrust 2.0, was used to quantify effective fishing effort and define geographic patterns of fishing activity. VMS-based species-specific effort from 2003 was integrated with landings to estimate landings per unit effort (landings per day at sea and landings per hour trawled. Integration of cephalopod size-classes data with VMS information enabled the estimation of size-dependent effort and analysis of geographical patterns of population structure. A group of vessels with landing activity and VMS coverage of trips belonging to distinct LP were selected to constitute a potential sample fleet for estimating speciesdirected LPUE. Their representativeness in terms of effort and LPUE was examined by comparing these results with those obtained for the entire fleet. This reduced fleet was found to be a possible candidate for a sampling programme under the EU Data collection Framework. Overall findings highlight the benefits of combining fisheriesdependent data, to produce information relevant for integrated management, in accordance with the Common Fisheries Policy and Marine Strategy Framework Directive objectives.